Growing a new generation of music teachers - Burrack, Frederick W. (My University, 2010)
At a time when many veteran music teachers are retiring, an apprenticeship program can help high school students consider a music career and offers them increased chances of success in college and beyond. This article offers information about the Music Teacher Apprenticeship Program made available through Kansas State University Music Education Department.
Keywords: Music teachers; Apprenticeship; High school students; Music students